Bezugspersonenbelastung erwachsener Patienten mit sozialer Angststörung - Hunger-Schoppe, Christina; Hilzinger, Rebecca; Ditzen, Beate; Schweitzer, Jochen (Psychotherapeut, 2018)
BackgroundA desirable effect (spill-over effect) of patient-related psychotherapy refers to the reduction of burden of significant others. Most studies have concentrated on the significant others of patients with schizophrenia, psychosis and dementia, as well as on child and adolescent psychotherapy.ObjectiveThis study investigated the effects of Cognitive Behavioral Therapy (CBT) and Systemic Psychotherapy (ST) on the burden of significant others for adult patients with social anxiety disorder from the patient-related randomized controlled pilot study Systemic Therapy and Cognitive Behavioral Therapy for Social Anxiety Disorders With Adults: Manual Development and Randomized Controlled Pilot Study (SOPHO-CBT/ST).Material and methodsIn this study, 29 significant others were asked about their psychosocial burden (Burden Assessment Scale, BAS) and impairments due to psychological and physical symptoms (Brief Symptom Inventory, BSI) before and at the end of therapy of the patient.ResultsThe psychosocial burden (BAS) significantly decreased with medium effects (CBT: d = 0,56, ST: d = 0.59, p ≤ 0.050). The impairments due to mental and physical symptoms (BSI), which were already present in the normal range before starting therapy, showed no significant improvement.ConclusionThe study demonstrates that outpatient patient-oriented psychotherapy with predominantly only one member (patient) of the affected social system can contribute to the reduction of psychosocial burden of significant others. It complements studies on interventions explicitly addressing significant others. A more strongly powered and confirmatory randomized controlled trial is needed to examine whether potential treatment-related differences were masked. This could be due to the small number of patients in this study, which however showed sufficient power for a randomized controlled pilot study.